Os descaminhos da docência : narrativas de egressos de curso de licenciatura em matemática que não exercem a profissão - Reisdoefer, Deise Nivia (2020)
The main objective of this study is to understand the expectations of a group of graduates from a Mathematics Licentiate Degree course at a Federal Teaching Institution in relation to the teaching career, as well as their motivations for giving up the profession. The problem that directs the investigation is: What are the reasons that contributed so that egress students of a licentiate course did not pursue the teaching career? Methodologically, the study is based on narrative research (CLANDININ; CONNELLY, 2015), which prioritizes experience and considers three-dimensional space, whose terms are interaction, continuity and situation. Thus, thinking, reading, writing, interpreting and analysing narratively required and allowed movement in four directions: both forward (prospectively), backward (retrospectively), inward (introspectively) and outward (extrospectively). The research results were organized and presented in the form of field texts and research texts. The construction of the field texts took place in an interpretative way and was divided into two parts: in the first, I introduce the six graduates based on their professors’ reports, on my memories and on documents from when they were undergraduate students; in the second, I present the crônicas constructed and organized from the interviews with the graduates. Subsequently, I present the research texts, which result from an analytical-interpretative process of the information contained in the field texts and which originated the Dimensions of Teaching Abandonment. Such research texts comprise my narrative as a professor of the group of graduates and balance their stories, my memories and experiences and the most appropriate theoretical framework to each of five dimensions: (1) Political-Financial Dimension, in which I highlight the importance that a federal institution of education in the countryside allowed the Graduates to attend Higher Education and the issues of lacking job security and devaluation as motivators for career abandonment; (2) Pedagogical Dimension, in which I analysed the stories related to the courses taken in the degree, especially those in the area of Mathematics, considered scarce, and those in the Pedagogical area, considered excessive; (3) Affective Dimension, in which the relationships established during the undergraduate course, with their classmates and professors, appear as important explanations for, on the one hand, remaining in the degree until its completion and, on the other, for professional choices not related to teaching; (4) Dimension of Formative Practice, which allowed the analysis of the experiences of the graduates in the field of practice during the practices as a curricular component and internships, whose stories demonstrate bad and inadequate experiences and a view of teacher as a suffering professional; and (5) Professional Dimension, in which I gather the stories about the academic and professional choices made by the graduates after completing their degree, their influence on personal and professional life, and also a reflection on who they are and how they assume, or not, the teaching profession. A common point in all dimensions and with different analyses, the figure of the teacher has become an important element of interpretation and analysis. The most significant components, which appeared in all dimensions, are aimed at this professional figure. The teacher was highlighted as a common subject, a specific person in a particular history, or as a group, such as professors and Basic Education teachers, or, more broadly, as the professional teacher with endless tasks and devalued by the state and society. Experimental and relational factors, centered on the figure of the teacher, are components that contributed to flaws in the teacher constitution or to disenchantment and displeasure with the profession, thus stimulating this group of graduates to abandon the teaching career as soon as the degree was completed.